In a blink - Thorpe, Kiki (Thorpe, Kiki. Never girls, 2013)
When four friends are whisked out of their ordinary lives to Never Land, home to fairies and mermaids, Queen Clarion and Tinker Bell have to figure out a way for them to get home.